Impact of the Scottish Reduction in Antimicrobial Prescribing (ScRAP) Programme on primary care prescribing for urinary tract infection (UTI). Issue 2 (28th February 2020) - Sneddon, Jacqueline; Thomson, Anne; Malcolm, William; Baxter, Linsey
Abstract : Introduction The ScRAP programme was developed as a national initiative to support improvements in managing patients presenting with symptoms of UTI. The programme comprises educational content plus improvement ideas. It was implemented in one large, mainly urban, NHS board region covering 21% of the Scottish population via Prescribing Support Pharmacists working with individual GP Practices. A key aim was to reduce unnecessary antibiotic use. Method: A facilitated learning session was delivered and all clinical and non-clinical GP Practice staff, were invited to attend. Evidence supporting best practice in managing UTI, local prescribing data and local practice was considered and discussed. The session concluded with action planning to reflect on current practice and identify areas for improvement. National data held by NHS National Services Scotland was used to evaluate prescribing across all NHS board regions in Scotland focusing on total use of antibiotics and use of trimethoprim and nitrofurantoin which are used solely for UTI. Results: Analysis of national prescribing data comparing the implementation region with the rest of Scotland suggests the intervention has been successful. Comparing data from prior to and for one year after the intervention period reductions for the intervention board versus the rest of Scotland were as follows: all antibiotics 7.29% vs 6.11%; trimethoprim 6.14% vs 3.73%; nitrofurantoin 3.92% vs 0.56%. Conclusion: Quantitative evaluation provides evidence of the impact of ScRAP on prescribing rates. This suggests that improved practice has led to reduction in unnecessary use of antibiotics for acute and recurrent UTI.